Unusual Presentation of Acute Gastrointestinal Bleeding in Gastric Lipoma and Concomitant Helicobacter pylori Infection: A Case Report - Amey Joshi; Rohan Kumar; Maitri Shah; Ryan Mui; Tadd Kaeo Hiatt (Clinical Case Reports)
ABSTRACT Active Helicobacter pylori (H. pylori) infection may contribute to the ulceration and hemorrhage of otherwise benign gastric lipomas. This case highlights the utility of combining invasive and non‐invasive testing of H. pylori in bleeding gastric ulcers and emphasizes the critical role of H. pylori testing and eradication in bleeding gastric lipomas.